Effectiveness of a Formal Business of Ophthalmology Course for Trainees - Siktberg, Jonathan; de Castro-Abeger, Alexander; Berkowitz, Sean T.; Law, Janice C. (Journal of Academic Ophthalmology, 2023)
Objective In medical school and residency training, there is little emphasis on the administrative and business aspects of running a clinical practice as either an employee or a business owner. However, by the first day of practice, young ophthalmologists need to have a basic understanding of the business of medicine to be successful in clinical practice and to avoid common pitfalls. Areas such as risk management, negotiation, financial health, lawsuits, marketing, coding, and professionalism are particularly important for practicing ophthalmologists to grasp. We instituted a formal practice management course to increase the early exposure of our trainees to the business aspects of ophthalmology.Methods Ophthalmology trainees engaged in 11, 1-hour sessions over 3 weeks during a practice management course covering 10 of the most relevant business topics for early career ophthalmologists. A precourse needs assessment, and a postcourse satisfaction and outcomes survey were administered.Results Of the 24 trainees who completed the presurvey, 96% of respondents had no previous training in contract negotiation, 88% lacked training in lawsuits, and 88% had no training in liability insurance. 96% had no inpatient coding education, and 88% had no outpatient coding training. Seventeen trainees completed the postsurvey, and statistically significant improvements in confidence ratings were found in all domains including coding, malpractice claims, and building a practice. 88% of trainees reported that the course improved their ability to code, and 100% agreed that the course improved their understanding of lawsuits, ability to negotiate a contract, and their understanding of the business of ophthalmology.Conclusion A formal, targeted business of ophthalmology course improved the knowledge of trainees on essential business concepts. This course can serve as a model for other programs looking to meet this educational need.
Keywords: business of ophthalmology; practice management; residency education; malpractice; negotiation